2004
DOI: 10.1248/jhs.50.556
|View full text |Cite
|
Sign up to set email alerts
|

Novel Estrogenic Microsomal Metabolites from Phthalate Esters

Abstract: Many researchers have found evidence of the estrogenic effects of phthalate esters (PEs), but the disruption mechanism is not fully elucidated. Once PEs are hydroxylated at the ring 4-position, the resulting compounds exhibit unequivocal binding affinity for human estrogen receptors. In this study, we first succeeded to demonstrate the generation of potent estrogenic metabolite from PEs. We used rat liver microsomes and dimethyl phthalate (DMP) as a representative for the metabolism of PEs. Among the metabolit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…[36][37][38] In addition to being metabolized through hydrolysis, PEs can be produced ring-or alkyl chainhydroxylated metabolites. [40][41][42][43] Using several oxidized metabolites of DBP and DEHP (Fig. 1), we examined the coactivator-recruiting activity of human PPARα/γ (hPPARα/γ).…”
Section: Ppar-mediated Effects Of Hydroxylated Phthalate Estersmentioning
confidence: 99%
See 1 more Smart Citation
“…[36][37][38] In addition to being metabolized through hydrolysis, PEs can be produced ring-or alkyl chainhydroxylated metabolites. [40][41][42][43] Using several oxidized metabolites of DBP and DEHP (Fig. 1), we examined the coactivator-recruiting activity of human PPARα/γ (hPPARα/γ).…”
Section: Ppar-mediated Effects Of Hydroxylated Phthalate Estersmentioning
confidence: 99%
“…Novel metabolites resulting from microsomal metabolism of DMP have also been identified. 43) Based upon UV spectra and GC/MS analyses, these microsomal metabolites were identified as ring 3-or 4-hydroxylated DMP. The potent ER-mediated activity of PEs-4OH suggests that PEs acquire ER-mediated activity via metabolic processing.…”
Section: Microsomal Metabolismmentioning
confidence: 99%
“…For example, differences in alkyl chain lengths and branching are associated with drastic differences in the estrogen receptor (ER)-mediated effects of ring-hydroxylated PEs, which are active metabolites/photo-oxidation products of PEs and are bound to ERs. [7][8][9][10] The ER-binding potential of ring-hydroxylated PEs increases with increasing alkyl chain length and branching. A yeast reporter gene assay revealed that PEs with short alkyl chains (e.g., ethyl or propyl esters) promoted ERdependent reporter gene expression, whereas PEs with long alkyl chains (e.g., octyl or 2-ethylhexyl esters) did not, even though the latter exhibited extremely high ER-binding affinities.…”
Section: Introductionmentioning
confidence: 99%